Dominance and diversity studies of tree species in lesser Himalayan forest of Uttarakhand, India - A. S. BISHT; A. B. BHATT (Society for Indonesian Biodiversity, 2016)
Bisht AS, Bhatt AB. 2016. Dominance and diversity studies of tree species in lesser Himalayan forest of Uttarakhand, India. Biodiversitas 17: 70-77. For the present investigation single mountain, approach was applied. This is a supplement the basic approach and extends the gradients further downward in to the forest belt. Vegetational analysis of nine stands covering all the four aspects of the study site of Pauri Garhwal district of Uttarakhand, India has been undertaken. In seven trees, species were encountered. East aspect is characteristics by highest density of Cupressus torulosa while west aspect comprised of Cedrus deodara, Myrica esculenta, Pinus.roxbugrhii, Quercus leucotrichophora and Rhododendron arboreum, i.e.high diversity with low dominance Cupressus torulosa and Cedrus deodara dominated the north aspect. In general, influence of higher anthropogenic pressure on Quercus species is an important factor for leads to gradual replacement of oak species by Pinus roxburghii in all the aspects.